Cinedesign: typography in motion pictures - Las-Casas, Luiz Fernando (InfoDesign, 2007)
An overview of the major work, a doctoral dissertation, Cinedesign: typography and graphic design in motion pictures (2006), where the elements and principles of audiovisual design are analyzed in two great categories of graphic design in the movies, i.e., Narrative Typography and Informational Typography. Cinedesign is part of audiovisual design, a major branch of graphic design, resulting from the combination of graphic images with action images and sound. Visual communication methods and processes merge with narrative techniques in order to convey and communicate ideas and feelings.